Nile tilapia, Oreochromis niloticus, productive performance and carcass characteristics as related to food management - Baccarin, Ana Eliza [UNESP]; Monteiro Camargo, Antonio Fernando [UNESP] (Taylor & Francis, 2004)
Male juveniles of Nile tilapia, Oreochromis niloticus, were stocked in 12, 300-m 2 ponds at a density of 1.7 fish/m 2 to evaluate the effects of different food management methods (natural foods and diets in pellet, floating or minced form) on fish production and carcass characteristics. Water quality variables monitored during the period were within acceptable levels for the species. Total fish production was significantly different (P < 0.05) and the highest values were obtained with diets in pellet (5,997 kg/ha) and floating (5,441 kg/ha) form. The fish fed diets had higher contents of body fat (1.57 to 1.98%) and visceral fat (12.64 to 25.04%) than fish fed natural food, which had levels between 0.17 and 0%, respectively. Natural food treatment yielded lower fish production and fish with lower body fat, while treatments that yielded higher fish production (rations) higher percentage of visceral fat. © 2004 by The Haworth Press, Inc. All rights reserved.
Keywords: Carcass characteristic; Fish production; Food management; Nile tilapia; Oreochromis niloticus; aquaculture production; artificial diet; fish culture; Tilapia